Interaction of magnetic nanoparticles with phospholipid films adsorbed at a liquid/liquid interface - Cámara, Candelaria Inés (2014)
The interaction of Co hexagonal magnetic nanoparticles (MNPs) with distearoyl phosphatidyl glycerol(DSPG) and distearoyl phosphatidic acid (DSPA) films adsorbed at a water/1,2-dichloroethane interface isstudied employing cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), capacitycurves and interfacial pressure–area isotherms. DSPA and DSPG adsorb at the interface forming homo-genous films and producing a blocking effect on the transfer process of tetraethyl ammonium (TEA+),used as a probe cation. In the presence of Co NPs this effect is reversed and the reversible transferprocess for TEA+is reestablished, to a greater or lesser extent depending on the structuration of the film.Co–DSPA hybrid films have a homogeneous structure while Co-DSPG films present different domains.Moreover, the presence of Co on DSPA film modifies the partition coefficient of the organic electrolyteinto the hydrocarbon layer.